The TED spread as a risk factor in the cross section of stock returns - Westrupp, Victor (2012)
We provide empirical evidence of the TED spread as a risk factor in the cross-section of stock returns. Portfolios with high sensitivities to the TED spread have high average risk-adjusted returns. The pricing of TED spread risk is especially strong among small caps. TED spread is a usual measure of funding difficulties in interbank markets and our results are consistent with the Margin-CAPM model of Garleanu and Pedersen (2011).